A Feedforward Decoupling Control Method for Multi-ports DC Transformer. Issue 1 (January 2021) - Wu, Hao
Abstract: DC Transformer (DCT) is a new type of intelligent power electronic device using power semiconductors and high-frequency transformer to realize power conversion. Multi-ports DCT has broad applications in DC distribution networks. In this paper, the power transmission characteristics of the phase-shift controlled multi-ports DCT are analyzed. The non-linear coupling characteristics of the output power at different ports are also studied. The small-signal dynamic coupling model of the multi-ports DCT is established. On this basis, a feed-forward term is introduced and constructed in the closed-loop voltage control system. The theoretical analysis shows that the feedforward term can decouple the output voltage of different ports of the multi-ports DCT. The correctness of the feed-forward control method is verified by simulations.